Utilizing Pragmatism Approach in Learning Jazz Guitar Reharmonization Technique using Malay Asli Song (Universitas Negeri Semarang, 2020)
Details of developing jazz guitar reharmonization learning book using Malay Asli song will not discuss here, however, this article divulges pragmatism approach that can be transcending in explaining logic between learning jazz guitar reharmonization techniques using Malay Asli Song. Although music is a universal language, traditional music and western music educators do not come to an agreement diffusing learning western music elements such in traditional music or vice versa. As a result, reharmonization technique only become known on western music repertoires. While traditional music practitioners presenting the same old repertoires, with deep-rooted dogmatic excuses to maintain what they called traditional authentic values. To conduct this study, relevant data on pragmatism was done through document analysis. The result show pragmatism approach can help music educators to reconceptualize teaching and learning traditional music using jazz reharmonization technique to recreate and innovate a new sound and contextual of learning jazz harmony, not just using on jazz standards repertoires, in making music theory beneficial to both traditional and modern music educators and students.